Thermoplastic resin composition, method for preparing the same, and molded article containing the same

By using a combination of alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer and polymethacrylate resin in a specific proportion in the ASA resin, the problem of inconsistent whitening and mechanical properties of ASA resin is solved. Excellent mechanical properties and non-albinding properties are achieved, and the transparency and colorability of the product are improved.

CN115119513BActive Publication Date: 2024-12-13LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180009660.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-01-22
Filing Date
2021-12-14
Publication Date
2024-12-13
Estimated Expiration
2041-12-14

AI Technical Summary

Technical Problem

The existing ASA resin is prone to whitening during the modification process, resulting in deterioration of appearance, and is inconsistent with the mechanical properties of conventional resins, making it difficult to meet the requirements of excellent transparency and colorability.

Method used

By adjusting the coverage value and rubber using a combination of 35-85% alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer and 15-65% polymethacrylate resin The particle size forms a thermoplastic resin composition with excellent mechanical properties and non-albinding properties.

Benefits of technology

Excellent mechanical properties, transparency and coloring properties of the thermoplastic resin composition are achieved, and whitening is prevented during bending, thereby enhancing the aesthetics and usability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115119513B_ABST
    Figure CN115119513B_ABST
Patent Text Reader

Abstract

The present invention relates to a thermoplastic resin composition, a method for preparing the same and a molded product including the same. More specifically, the present invention relates to a thermoplastic resin composition, a method for preparing the thermoplastic resin composition and a molded product including the thermoplastic resin composition, comprising 35% to 85% by weight of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A) and 15% to 65% by weight of a polymethacrylate resin (B), wherein the graft copolymer (A) contains an alkyl acrylate rubber having an average particle size of 50nm to 120nm, wherein the alkyl acrylate coverage value (X) calculated by equation 1 of the thermoplastic resin composition is 70% or more. According to the present invention, the present invention has the following effects: providing a thermoplastic resin composition, a method for preparing the thermoplastic resin composition and a molded product including the thermoplastic resin composition, the thermoplastic resin composition having excellent mechanical properties such as impact strength, tensile strength and flexural strength, surface hardness, transparency and colorability, and being able to prevent whitening during bending due to excellent non-whitening properties.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the priority of Korean Patent Application No. 10-2021-0009292 filed on January 22, 2021, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference. Technical Field

[0003] The present invention relates to a thermoplastic resin composition, a method for preparing the same, and a molded article comprising the same. More specifically, the present invention relates to a thermoplastic resin composition having excellent mechanical properties such as impact strength, tensile strength and flexural strength, surface hardness, transparency and colorability, and capable of preventing whitening during bending due to excellent non-whitening properties, a method for preparing the same, and a molded article comprising the same. Background Art

[0004] Acrylate-styrene-acrylonitrile copolymer (hereinafter referred to as "ASA resin") has excellent weather resistance, aging resistance, chemical resistance, rigidity, impact resistance and processability, and is widely used in various fields such as automobiles, groceries and building materials due to its wide applicability.

[0005] Furthermore, as the importance of aesthetics increases in the market, research is being conducted on methods of modifying the surfaces of substrates (e.g., acrylonitrile-butadiene-styrene resins, polyvinyl chloride resins, polyethylene terephthalate resins, and iron plates) with ASA resin compositions in order to achieve an aesthetically pleasing appearance and excellent colorability and weather resistance.

[0006] However, due to the characteristics of ASA resin, when the modification process is carried out, depending on the shape of the product, whitening occurs on the surface of the product during processes such as cutting, bending and molding, resulting in loss of original color and deterioration of appearance. The whitening is caused by the voids generated by the cracks inside the ASA resin. In order to solve this problem, a method of softening the resin by increasing the rubber content has been used. However, due to the different mechanical properties from conventional ASA resin compositions, there are limitations in use.

[0007] Therefore, there is a need to develop a thermoplastic resin composition which has excellent transparency and colorability, has mechanical properties and surface hardness similar to those of a conventional ASA resin composition, and is capable of preventing whitening from occurring.

[0008] Prior art literature

[0009] Patent Literature

[0010] Japanese Patent No. 1995-033470 Summary of the invention

[0011] Technical issues

[0012] Therefore, the present invention has been made in view of the above problems, and an object of the present invention is to provide a thermoplastic resin composition which has excellent mechanical properties such as impact strength, tensile strength and flexural strength, surface hardness, transparency and colorability, and can prevent whitening during bending due to excellent non-whitening properties.

[0013] Another object of the present invention is to provide a method for preparing the thermoplastic resin composition.

[0014] Another object of the present invention is to provide a molded article produced using the thermoplastic resin composition.

[0015] The above and other objects can be achieved by the present invention described below.

[0016] Technical Solution

[0017] According to one aspect of the present invention, there is provided a thermoplastic resin composition, comprising: 35 wt % to 85 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm; and 15 wt % to 65 wt % of a polymethacrylate resin (B), wherein the thermoplastic resin composition has an alkyl acrylate coverage value (X) of 70% or more as calculated by the following equation 1:

[0018] [Equation 1]

[0019] X = {(GY) / Y} × 100,

[0020] wherein G represents the gel content (wt%) based on the total weight of the thermoplastic resin composition, and Y represents the content (wt%) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition.

[0021] In addition, the present invention can provide a thermoplastic resin composition, comprising: 35 wt % to 85 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A), which contains an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm; and 15 wt % to 65 wt % of a polymethacrylate resin (B), wherein the weight average molecular weight of the polymethacrylate resin (B) is 50,000 g / mol to 150,000 g / mol.

[0022] In addition, the present invention can provide a thermoplastic resin composition, comprising: 35 to 85 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A), which contains an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm; and 15 to 65 wt % of a polymethacrylate resin (B), wherein the thermoplastic resin composition has a total light transmittance (Tt) of 75% or more when measured using a test specimen having a thickness of 3T according to ASTM D1003.

[0023] According to another aspect of the present invention, there is provided a method for preparing a thermoplastic resin composition, comprising kneading and extruding 35 wt % to 85 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A) and 15 wt % to 65 wt % of a polymethacrylate resin (B) at 200° C. to 300° C. and 100 rpm to 500 rpm, the graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm, wherein the thermoplastic resin composition has an alkyl acrylate coverage value (X) calculated by the following equation 1 of 70% or more,

[0024] [Equation 1]

[0025] X = {(GY) / Y} × 100,

[0026] wherein G represents the gel content (wt%) based on the total weight of the thermoplastic resin composition, and Y represents the content (wt%) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition.

[0027] In addition, the present invention can provide a method for preparing a thermoplastic resin composition, which comprises kneading and extruding 35 wt % to 85 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A) and 15 wt % to 65 wt % of a polymethacrylate resin (B) at 200° C. to 300° C. and 100 rpm to 500 rpm, wherein the graft copolymer (A) contains an alkyl acrylate rubber having an average particle diameter of 50 nm to 120 nm, wherein the polymethacrylate resin (B) has a weight average molecular weight of 50,000 g / mol to 150,000 g / mol.

[0028] In addition, the present invention can provide a method for preparing a thermoplastic resin composition, which comprises kneading and extruding 35 wt % to 85 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A) and 15 wt % to 65 wt % of a polymethacrylate resin (B) at 200° C. to 300° C. and 100 rpm to 500 rpm, wherein the graft copolymer (A) contains an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm, wherein the thermoplastic resin composition has a total light transmittance (Tt) of 75% or more as measured using a test specimen having a thickness of 3T according to ASTM D1003.

[0029] According to still another aspect of the present invention, there is provided a molded article including the thermoplastic resin composition.

[0030] Beneficial Effects

[0031] According to the present invention, there are provided a thermoplastic resin composition having excellent mechanical properties such as impact strength, tensile strength and flexural strength, surface hardness, transparency and colorability and capable of preventing whitening during bending due to excellent non-whitening properties, a method for preparing the thermoplastic resin composition, and a molded article comprising the thermoplastic resin composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 An image showing whether whitening occurs on a curved surface formed when the extruded sheet specimens having a thickness of 0.15T manufactured in Examples 1, 2, 4, and 5 of the present invention and Comparative Examples 2 to 5 are manually folded. DETAILED DESCRIPTION

[0033] Hereinafter, a thermoplastic resin composition according to the present invention, a method for preparing the same, and a molded article including the same will be described in detail.

[0034] The present inventors have confirmed that when an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer containing a rubber having a predetermined average particle size and a polymethacrylate resin are mixed at a predetermined composition ratio and the alkyl acrylate coverage value is adjusted within a predetermined range, mechanical properties, surface hardness, transparency and colorability are improved compared to conventional ASA-based resins, and whitening is prevented from occurring due to excellent non-whitening properties. Based on these results, the present inventors have conducted further studies and completed the present invention.

[0035] The thermoplastic resin composition of the present invention comprises 35 to 85 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A) and 15 to 65 wt % of a polymethacrylate resin (B), wherein the graft copolymer (A) contains an alkyl acrylate rubber having an average particle size of 50 to 120 nm, wherein the thermoplastic resin composition has an alkyl acrylate coverage value (X) calculated by equation 1 of 70% or more. In this case, excellent mechanical properties such as impact strength, tensile strength and flexural strength, surface hardness, transparency and colorability can be obtained. In particular, due to the excellent non-whitening property, whitening during bending can be prevented.

[0036] [Equation 1]

[0037] X = {(GY) / Y} × 100,

[0038] In Equation 1, G represents the gel content (weight %) based on the total weight of the thermoplastic resin composition, and Y represents the content (weight %) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition.

[0039] Hereinafter, each component constituting the thermoplastic resin composition of the present invention will be described in detail.

[0040] (A) Alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer

[0041] For example, the graft copolymer (A) may contain an alkyl acrylate rubber having an average particle size of 50 to 120 nm, preferably 60 to 120 nm, and more preferably 80 to 110 nm. Within this range, the finally prepared thermoplastic resin composition may have excellent impact strength, light resistance and gloss.

[0042] In this specification, the average particle size can be measured by dynamic light scattering, and specifically, can be measured as an intensity value using a particle size analyzer (product name: Nicomp 380, manufacturer: PSS) in Gaussian mode. As a specific measurement example, a sample can be prepared by diluting 0.1 g of latex (total solid content: 35 to 50% by weight) by 1,000 to 5,000 times with distilled water, and the average particle size can be measured using a flow cell in an automatic dilution mode in a dynamic light scattering / intensity 300kHz / intensity-weighted Gaussian analysis mode. At this time, the temperature can be set to 23°C, the measurement wavelength can be set to 632.8nm, and the channel width can be set to 10μsec.

[0043] For example, based on the total weight of components (A) and (B), the content of the graft copolymer (A) may be 35 to 85 wt %, preferably 40 to 80 wt %, more preferably 50 to 80 wt %, still more preferably 60 to 80 wt %, still more preferably 60 to 75 wt %. Within this range, excellent mechanical properties such as impact strength, tensile strength and flexural strength, gloss and surface hardness may be achieved.

[0044] For example, the graft copolymer (A) may contain 20 to 60% by weight of the alkyl acrylate rubber (a-1) and 40 to 80% by weight of the aromatic vinyl compound-vinyl cyanide copolymer (a-2), preferably 30 to 50% by weight of the alkyl acrylate rubber (a-1) and 50 to 70% by weight of the aromatic vinyl compound-vinyl cyanide copolymer (a-2), more preferably 40 to 50% by weight of the alkyl acrylate rubber (a-1) and 50 to 60% by weight of the aromatic vinyl compound-vinyl cyanide copolymer (a-2). Within this range, excellent mechanical properties, glossiness and surface hardness can be achieved.

[0045] For example, the alkyl acrylate rubber can be prepared by emulsion polymerization of alkyl acrylate. As a specific example, the alkyl acrylate rubber can be prepared by mixing alkyl acrylate, emulsifier, initiator, grafting agent, crosslinking agent, electrolyte and solvent and performing emulsion polymerization of the mixture. In this case, it can have excellent grafting efficiency and thus can have excellent physical properties such as impact resistance.

[0046] In the present specification, a polymer including a certain compound means a polymer prepared by polymerizing the compound, and a unit in the polymer is derived from the compound.

[0047] For example, the alkyl acrylate rubber (a-1) may further include an aromatic vinyl compound. In this case, chemical resistance and impact resistance may be further improved. For example, based on a total of 100% by weight of the acrylate rubber, the alkyl acrylate rubber (a-1) may include an aromatic vinyl compound having a content of 0.1% to 35% by weight, preferably 1% to 30% by weight, more preferably 7% to 30% by weight, and even more preferably 10% to 20% by weight. Within this range, excellent mechanical properties, glossiness and surface hardness may be obtained, and physical properties may not deteriorate.

[0048] For example, the copolymer (a-2) may further include an alkyl acrylate. In this case, excellent physical property balance among impact resistance, weather resistance, processability, and non-whitening property may be achieved.

[0049] For example, based on 100 wt % of the total copolymer (a-2), the copolymer (a-2) may include 55 wt % to 85 wt % of the aromatic vinyl compound, 10 wt % to 30 wt % of the vinyl cyanide and 0.1 wt % to 35 wt % of the alkyl acrylate, preferably 60 wt % to 80 wt % of the aromatic vinyl compound, 15 wt % to 25 wt % of the vinyl cyanide and 1 wt % to 25 wt % of the alkyl acrylate, more preferably 65 wt % to 75 wt % of the aromatic vinyl compound, 15 wt % to 22 wt % of the vinyl cyanide and 5 wt % to 20 wt % of the alkyl acrylate. Within this range, impact resistance and weather resistance can be further improved.

[0050] For example, the graft copolymer (A) may be prepared by emulsion polymerization. In this case, excellent gloss and surface hardness may be obtained.

[0051] For example, the alkyl acrylate may be an alkyl acrylate containing an alkyl group having 1 to 15 carbon atoms, preferably including one or more selected from the group consisting of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylbutyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, hexyl acrylate, heptyl acrylate, n-pentyl acrylate, and lauryl acrylate. More preferably, the alkyl acrylate is an alkyl acrylate having 2 to 8 carbon atoms, more preferably butyl acrylate, ethylhexyl acrylate, more preferably butyl acrylate.

[0052] For example, the aromatic vinyl compound may include one or more selected from the group consisting of styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, ethylstyrene, isobutylstyrene, tert-butylstyrene, o-bromostyrene, p-bromostyrene, m-bromostyrene, o-chlorostyrene, p-chlorostyrene, m-chlorostyrene, vinyltoluene, vinylxylene, fluorostyrene and vinylnaphthalene, preferably one or more selected from the group consisting of styrene and α-methylstyrene, more preferably styrene. In this case, due to appropriate fluidity, it can have excellent processability and can have excellent mechanical properties such as impact resistance.

[0053] For example, the vinyl cyanide may include one or more selected from the group consisting of acrylonitrile, methacrylonitrile, ethacrylonitrile, and isopropylacrylonitrile, preferably acrylonitrile.

[0054] An emulsion polymerization method generally practiced in the art to which the present invention pertains can be used in the present invention without particular limitation.

[0055] For example, the graft copolymer (A) may have a grafting degree of 60% to 150%, preferably 62% to 140%, more preferably 65% ​​to 130%, and still more preferably 65% ​​to 100%, as calculated by the following Equation 3. Within this range, excellent gloss, colorability, and transparency may be achieved.

[0056] [Equation 3]

[0057] Grafting degree (%) = [grafting monomer weight (g) / rubber weight (g)] × 100

[0058] In Equation 3, the weight (g) of the grafted monomer is obtained by subtracting the rubber weight (g) from the weight of the insoluble matter (gel) obtained by dissolving the grafted copolymer in acetone and centrifuging it, and the rubber weight (g) is the weight (g) of the rubber component theoretically added to the grafted copolymer powder.

[0059] When measuring the weight of insoluble matter (gel), 0.5 g of powdered graft copolymer (A) was added to 50 ml of acetone and then stirred at room temperature for 12 hours. Then, centrifugation was performed to separate the insoluble matter that was insoluble in acetone and then dried for 12 hours. Then, the weight of insoluble matter (gel) was measured. The rubber weight (g) is the weight (g) of the rubber component theoretically added to 0.5 g of powdered graft copolymer (A).

[0060] As a specific measurement example, when measuring the weight of insoluble matter (gel), 0.5 g of powdered graft copolymer was added to 50 ml of acetone, and then stirred for 12 hours using an orbital shaker (equipment name: Labcompanion SKC-6075) at 210 rpm and room temperature. Then, centrifuge (Supra R30, Hanil Scienece) was used to centrifuge for 3 hours at 0° C. and 18,000 rpm to separate the insoluble matter in acetone, and then dried for 12 hours by forced circulation in a forced convection oven (equipment name: Lab companion OF-12GW) set at 85° C. Then, the weight of the insoluble matter (gel) was measured.

[0061] (B) Polymethacrylate resin

[0062] For example, based on the total weight of components (A) and (B), the content of polymethacrylate resin (B) may be 15% to 65% by weight, preferably 20% to 60% by weight, more preferably 20% to 50% by weight, still more preferably 20% to 40% by weight, still more preferably 25% to 40% by weight. Within this range, excellent mechanical properties such as impact strength, tensile strength and flexural strength, surface hardness, transparency and colorability may be achieved. In particular, due to the excellent non-whitening property, whitening during bending may be prevented.

[0063] For example, the polymethacrylate resin (B) may have a weight average molecular weight of 50,000 g / mol to 150,000 g / mol, preferably 60,000 g / mol to 140,000 g / mol, more preferably 70,000 g / mol to 130,000 g / mol, and still more preferably 80,000 g / mol to 120,000 g / mol. Within this range, weather resistance may be further improved, and excellent tensile strength and impact strength may be obtained.

[0064] In this specification, unless otherwise defined, weight average molecular weight can be measured using gel permeation chromatography (GPC, Waters Breeze). As a specific example, weight average molecular weight can be measured by gel permeation chromatography (GPC, Waters Breeze) using tetrahydrofuran (THF) as eluent. In this case, weight average molecular weight is obtained as a relative value relative to a polystyrene (PS) standard sample. As a specific measurement example, the weight-average molecular weight can be measured under the following conditions: THF, column temperature: 40°C, flow rate: 0.3 ml / min, sample concentration: 20 mg / ml, injection volume: 5 μl, column mode: 1×PLgel 10 μm MiniMix-B (250×4.6 mm) + 1×PLgel 10 μm MiniMix-B (250×4.6 mm) + 1×PLgel 10 μm MiniMix-B Guard (50×4.6 mm), equipment name: Agilent 1200 series system, refractive index detector: Agilent G1362 RID, RI temperature: 35°C, data processing: Agilent ChemStation S / W, and test method: OECD TG 118.

[0065] The polymethacrylate resin (B) preferably includes the methacrylate monomer in an amount of 55% by weight or more, more preferably 60% by weight or more, and still more preferably 65% ​​by weight or more. Within this range, weather resistance can be greatly improved, and excellent gloss and colorability can be obtained.

[0066] For example, the methacrylate monomer may be an alkyl methacrylate containing an alkyl group having 1 to 15 carbon atoms, preferably including one or more selected from the group consisting of methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylbutyl methacrylate, 2-ethylhexyl methacrylate, and lauryl methacrylate. More preferably, the methacrylate monomer is an alkyl methacrylate containing an alkyl group having 1 to 4 carbon atoms, more preferably methyl methacrylate.

[0067] The polymethacrylate resin (B) preferably includes one or more selected from the group consisting of polymethyl methacrylate resins and methyl methacrylate-styrene-acrylonitrile copolymers. More preferably, the polymethacrylate resin (B) is polymethyl methacrylate resin or methyl methacrylate-styrene-acrylonitrile copolymer, more preferably polymethyl methacrylate resin. Within this range, weather resistance can be further improved, and excellent transparency and colorability can be obtained.

[0068] For example, the methyl methacrylate-styrene-acrylonitrile copolymer may include 65 wt % to 85 wt % of methyl methacrylate, 5 wt % to 30 wt % of styrene and 5 wt % to 10 wt % of acrylonitrile, preferably 70 wt % to 80 wt % of methyl methacrylate, 15 wt % to 25 wt % of styrene and 5 wt % to 10 wt % of acrylonitrile. Within this range, weather resistance can be further improved, and excellent transparency and colorability can be obtained.

[0069] For example, the methyl methacrylate-styrene-acrylonitrile copolymer may have a weight average molecular weight of 70,000 g / mol to 140,000 g / mol. Preferably, the weight average molecular weight of the methyl methacrylate-styrene-acrylonitrile copolymer is 70,000 g / mol to 90,000 g / mol, greater than 90,000 g / mol and less than or equal to 140,000 g / mol, or a combination thereof. Within this range, weather resistance can be further improved, and excellent tensile strength, flexural strength, and impact strength can be obtained.

[0070] The polymethacrylate resin (B) can be prepared by solution polymerization, bulk polymerization, emulsion polymerization or suspension polymerization. Solution polymerization, bulk polymerization, emulsion polymerization and suspension polymerization commonly practiced in the art to which the present invention belongs can be used in the present invention without particular limitation.

[0071] Thermoplastic resin composition

[0072] The thermoplastic resin composition of the present invention preferably has an alkyl acrylate coverage value (X) calculated by the following equation 1 of 70% or more, preferably 70% to 150%, more preferably 75% to 140%, still more preferably 80% to 130%, still more preferably 85% to 110%. Within this range, excellent transparency and colorability can be achieved. In particular, due to excellent non-whitening properties, whitening during bending can be prevented.

[0073] [Equation 1]

[0074] X = {(GY) / Y} × 100,

[0075] In Equation 1, G represents the gel content (weight %) based on the total weight of the thermoplastic resin composition, and Y represents the content (weight %) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition.

[0076] In Formula 1, the content of alkyl acrylate in the gel of the thermoplastic resin composition is the content of alkyl acrylate in the insoluble matter obtained in the process of measuring the gel content (based on a total of 100 wt % of the added thermoplastic resin composition). Here, the gel content is the content of the insoluble matter based on a total of 100 wt % of the thermoplastic resin composition.

[0077] The content of alkyl acrylate in the gel can be quantitatively measured by nuclear magnetic resonance (NMR) analysis or Fourier transform infrared spectroscopy (FT-IR) analysis.

[0078] In this specification, unless otherwise specified, NMR analysis refers to 1 HNMR analysis.

[0079] In the present specification, NMR analysis generally performed in the art can be used in the present invention, and specific measurement examples are as follows.

[0080] - Equipment name: Bruker 600MHz NMR (AVANCE III HD) CPP BB (1H 19F tunable, broadband, with z gradient) Prodigy probe

[0081] -Measurement conditions: 1 HNMR (zg30): ns=32, d1=5s, TCE-d2, at room temperature

[0082] In the present specification, FT-IR analysis generally performed in the art may be used in the present invention, and specific measurement examples are as follows.

[0083] -Device Name: Agilent Cary 660

[0084] -Measurement conditions: ATR mode

[0085] When measuring the gel content, 1g of the thermoplastic resin composition is added to 30g of acetone and then stirred at room temperature for 12 hours. Then, centrifugation is performed to separate the insoluble substances insoluble in acetone, and then dried for 12 hours. Then, the gel content is measured and calculated by the following equation 2. As a specific measurement example, when measuring the gel content, 1g of the thermoplastic resin composition is added to 30g of acetone, and then stirred for 12 hours using an orbital oscillator (equipment name: Lab companionSKC-6075) at 210rpm and room temperature. Then, a centrifuge (Supra R30, Hanil Scienece company) is used to centrifuge for 3 hours at 0°C and 18,000rpm to separate the insoluble substances insoluble in acetone, and then dried for 12 hours by forced circulation in a forced convection oven (equipment name: Lab companion OF-12GW) set at 85°C. Then, the gel content is measured.

[0086] [Equation 2]

[0087] Gel content (%) = [weight of insoluble matter (gel) (g) / weight of sample (g)] × 100

[0088] In this specification, the alkyl acrylate coverage value is a parameter for measuring the dispersion degree of the aromatic vinyl compound-vinyl cyanide polymer grafted onto the alkyl acrylate rubber in the thermoplastic resin composition. When the alkyl acrylate coverage value is high, the aromatic vinyl compound-vinyl cyanide polymer is uniformly grafted onto the alkyl acrylate rubber to uniformly cover the alkyl acrylate rubber, thereby increasing the glossiness and achieving excellent tensile strength and colorability. In addition, as the alkyl acrylate coverage value increases, the distance between rubber particles decreases, thereby reducing voids due to cracks occurring in the thermoplastic resin composition and suppressing whitening during bending.

[0089] In addition, the alkyl acrylate coverage value is obtained by quantitatively calculating the content of alkyl acrylate present in the thermoplastic resin composition by nuclear magnetic resonance (NMR) analysis or Fourier transform infrared spectroscopy (FT-IR) analysis, and the grafting degree is obtained based on the content of the rubber component added during polymerization.

[0090] Furthermore, the grafting degree is a parameter indicating the degree to which the aromatic vinyl compound-vinyl cyanide polymer is grafted onto the alkyl acrylate in the alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer.

[0091] For example, the thermoplastic resin composition can have a total light transmittance (Tt) of 75% or more, preferably 80% or more, more preferably 80% to 95%, and even more preferably 82% to 90%, as measured according to ASTM D1003 using a specimen having a thickness of 3T. Within this range, excellent physical property balance, transparency, colorability, and non-whitening properties can be achieved.

[0092] For example, the thermoplastic resin composition may have a haze of 11% or less, preferably 8% or less, more preferably 6% or less, and still more preferably 0.1% to 6%, measured according to ASTM D1003 using a specimen having a thickness of 3T. Within this range, excellent physical property balance, transparency, colorability, and non-whitening properties may be achieved.

[0093] For example, the thermoplastic resin composition may have a gloss of 120 or more, preferably 125 or more, more preferably 125 to 150, and still more preferably 133 to 145, measured using a gloss meter at an incident angle of 45° according to ASTM D2457. Within this range, excellent physical property balance, transparency, colorability, and non-whitening properties may be achieved.

[0094] For example, when a 1 kg weight is dropped vertically from a height of 25 cm onto an extruded film having a thickness, width, and length of 0.15 mm×5 cm×5 cm in size using a Gardner impact tester, the haze values ​​of the portion of the film hit by the weight before and after the impact are measured according to ASTM D1003, and the haze value difference is calculated, and the thermoplastic resin composition may have a haze difference (Δhaze) of 10 or less, preferably 8 or less, more preferably 5 or less, still more preferably 4 or less, still more preferably 3 or less, and still more preferably 0.1 to 3. Within this range, excellent physical property balance, appearance, and non-whitening properties may be exhibited.

[0095] For example, the Izod impact strength (specimen thickness: 1 / 4", room temperature) of the thermoplastic resin composition measured according to ASTM D256 may be 3 kgf·cm / cm or more, preferably 3.5 kgf·cm / cm or more, more preferably 3.5 kgf·cm / cm to 10 kgf·cm / cm, still more preferably 4 kgf·cm / cm to 9 kgf·cm / cm, still more preferably 4.5 kgf·cm / cm to 8.5 kgf·cm / cm. Within this range, excellent physical property balance and non-whitening properties can be achieved.

[0096] In this specification, the room temperature may be a temperature at 20±5°C.

[0097] For example, the tensile strength of the thermoplastic resin composition can be 200 kgf / cm2 when measured at a speed of 10 mm / min using a specimen having a thickness of 3.2 mm according to ASTM D638. 2Above, preferably 250kgf / cm 2 More preferably 300kgf / cm 2 More preferably 300kgf / cm 2 Up to 600kgf / cm 2 , more preferably 350kgf / cm 2 Up to 600kgf / cm 2 Within this range, excellent balance of physical properties and non-whitening properties can be achieved.

[0098] For example, the flexural strength of the thermoplastic resin composition may be 350 kgf / cm2 when measured according to ASTM D790 using a specimen having a thickness of 3.2 mm at a test speed of 10 mm / min with a span of 64 mm. 2 Above, preferably 450kgf / cm 2 More preferably 500kgf / cm 2 More preferably 500kgf / cm 2 Up to 900kgf / cm 2 Within this range, excellent balance of physical properties and non-whitening properties can be achieved.

[0099] For example, the thermoplastic resin composition may have a Rockwell hardness of 70 or more, preferably 80 or more, more preferably 80 to 110, as measured on an R scale according to ASTM D785. Within this range, indentation may be prevented from occurring, and an excellent balance of physical properties may be achieved.

[0100] If necessary, the thermoplastic resin composition may further include one or more components selected from the group consisting of heat stabilizer, light stabilizer, dye, pigment, colorant, lubricant, anti-adhesive agent, antistatic agent, antibacterial agent, processing aid, metal deactivator, flame retardant, smoke suppressant, anti-drip agent, anti-friction agent and anti-wear agent, each in an amount of 0.01 to 5 parts by weight, preferably 0.05 to 3 parts by weight, more preferably 0.1 to 2 parts by weight, and still more preferably 0.2 to 1.5 parts by weight, based on 100 parts by weight of the graft copolymer (A) and the polymethacrylate resin (B). Within this range, the desired physical properties of the thermoplastic resin composition of the present invention can be achieved without deteriorating its inherent physical properties.

[0101] Preferably, the heat stabilizer includes a primary heat stabilizer and a secondary heat stabilizer.

[0102] The primary heat stabilizer is preferably a phenolic heat stabilizer, and more preferably includes one or more selected from the group consisting of: 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 1,6-hexanediol bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2-thiodiethylene bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid diethyl ester, tris(2,6-dimethyl-3-hydroxy-4-tert-butylbenzyl) isocyanurate, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, tris[(3,5-di-tert-butyl-4-hydroxyphenyl) propionyloxyethyl] isocyanurate, tris(4-tert-butyl-2,6-dimethyl-3-hydroxybenzyl) isocyanurate, 2,2'-methylenebis(4-methyl-6-tert-butylphenol) terephthalate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 3,9-bis[1,1-dimethyl-2-{β-(3-tert-butyl-4-hydroxy-5-methyl)

[0013] Preferably, the esters are 2,2-bis[4-(2-3,5-di-tert-butyl-4-hydroxyhydrocinnamoyloxy)ethoxyphenyl]propane and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid stearyl ester, and 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid octadecyl ester (IR1076) is more preferably used.

[0103] The secondary heat stabilizer is preferably a phosphorus heat stabilizer, and more preferably includes one or more selected from the group consisting of: bis(dinonylphenyl)pentaerythritol diphosphite, phosphite, trioctyl phosphite, trilauryl phosphite, tridecyl phosphite, (octyl)diphenyl phosphite, tris(2,4-di-tert-butylphenyl)phosphite, triphenyl phosphite, tris(butoxyethyl) phosphite, tris(nonylphenyl) phosphite, distearyl pentaerythritol diphosphite, tetra(decyl) phosphite, trialkyl)-1,1,3-tri(2-methyl-5-tert-butyl-4-hydroxy-phenyl)butane diphosphite, tetra(C12-C15 mixed alkyl)-4,4'-isopropylidene diphenyl diphosphite, tetra(tridecyl)-4,4'-butylene bis(3-methyl-6-tert-butylphenol) diphosphite, tri(mononylphenyl and dinonylphenyl mixed) phosphite, hydrogenated 4,4'-isopropylidene diphenol polyphosphate, phenyl(4,4'-isopropylidene diphenyl) phenol) pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, tris[4,4'-isopropylidene bis(2-tert-butylphenol)]phosphite, di(isodecyl)phenyl phosphite, 4,4'-isopropylidene bis(2-tert-butylphenol)bis(nonylphenyl)phosphite, bis(2,4-di-tert-butyl-6-methylphenyl)ethyl phosphite, 2-[{2,4,8,10-tetra-tert-butyldibenzo[d,f][1.3.2]-dioxo-phosphacycloheptane-6 -yl}oxy]-N,N-bis[2-[{2,4,8,10-tetra-tert-butyl-dibenzo[d,f][1,3,2]-dioxaphosphine-6-yl}oxy]ethyl]-ethylamine and 6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1.3.2]-dioxaphosphine, and more preferably tris(2,4-di-tert-butylphenyl)phosphite (IF168).

[0104] The lubricant preferably includes one or more selected from the group consisting of aliphatic amide-based lubricants, fatty acid ester-based lubricants, and olefin-based waxes.

[0105] The aliphatic amide-based lubricant preferably includes one or more selected from the group consisting of stearamide, oleamide, erucamide, ethylenebisstearamide, and ethylenebisoleamide.

[0106] The fatty acid ester lubricant preferably includes one or more selected from the group consisting of fatty acid esters of alcohols or polyols, hardened oils, butyl stearate, monoglyceride stearate, pentaerythritol tetrastearate, stearyl stearate, ester waxes and alkyl phosphates.

[0107] The olefin wax is preferably polyethylene wax.

[0108] For example, the light stabilizer may include one or more selected from the group consisting of a HALS-type UV stabilizer and a benzotriazole-type UV stabilizer, preferably a mixture of a HALS-type UV stabilizer and a benzotriazole-type UV stabilizer.

[0109] The HALS-type UV stabilizer preferably includes one or more selected from the group consisting of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (UV770), bis[N-methyl-2,2,6,6-tetramethyl-4-piperidinyl] sebacate and dimethyl-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidinyl succinate (Tinuvin 622), more preferably bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (UV770).

[0110] The benzotriazole UV stabilizer preferably includes one or more selected from the following: 2-(2′-hydroxy-5′-tert-octylphenyl)-benzotriazole (Cyasorb UV-541), 2-(2′-hydroxy-5′-methylphenyl)benzotriazole (Tinuvin-P), 2-(2′-hydroxy-3′-tert-butyl-5′-methylphenyl)-5-chloro-benzotriazole (Tinuvin-326), 2-(2′-hydroxy-3′,5′-di-tert-butylphenyl)-5-chloro-benzotriazole (Tinuvin-327), 2-(2′-hydroxy-3,5-di-tert-pentylphenyl)benzotriazole (Tinuvin-328), 2-( 2′-Hydroxy-3′,5′-di(1,1-dimethylbenzyl)phenyl]-2H-benzotriazole (Tinuvin-234), 2-(2′-hydroxy-3′,5′-di-tert-butylphenyl)benzotriazole (Tinuvin-320) and 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (UV329), more preferably 2-(2H-benzotriazol-2-yl)-4-(1,3-tetramethylbutyl)phenol (UV329).

[0111] Method for preparing thermoplastic resin composition

[0112] The method for preparing the thermoplastic resin composition of the present invention comprises kneading and extruding 35 wt % to 85 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A) and 15 wt % to 65 wt % of a polymethacrylate resin (B) at 200° C. to 300° C. and 100 rpm to 500 rpm, wherein the graft copolymer (A) contains an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm, wherein the thermoplastic resin composition has an alkyl acrylate coverage value (X) calculated by the following equation 1 of 70% or more. In this case, excellent mechanical properties such as impact strength, tensile strength and flexural strength, surface hardness, transparency and colorability can be obtained. In particular, due to the excellent non-whitening property, whitening during bending can be prevented.

[0113] [Equation 1]

[0114] X = {(GY) / Y} × 100,

[0115] In Equation 1, G represents the gel content (weight %) based on the total weight of the thermoplastic resin composition, and Y represents the content (weight %) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition.

[0116] The method of preparing the thermoplastic resin composition shares all the technical features of the above-mentioned thermoplastic resin composition, and thus repeated description thereof will be omitted.

[0117] The kneading and extrusion steps are preferably performed using an extrusion kneader at 200° C. to 300° C. with a size of 10pi to 199pi, more preferably at 210° C. to 260° C. with a size of 20pi to 80pi, and more preferably at 220° C. to 250° C. with a size of 25pi to 75pi. Within this range, extrusion can be stably performed, and kneading can be performed efficiently. At this time, the temperature is the cylinder temperature, and pi represents the outer diameter of the screw (unit: mm).

[0118] An extrusion kneader commonly used in the field to which the present invention pertains may be used without particular limitation, and a twin-screw extrusion kneader is preferably used.

[0119] Molded products

[0120] The molded article of the present invention comprises the thermoplastic resin composition. In this case, it can have excellent mechanical properties such as impact strength, tensile strength and flexural strength, surface hardness, transparency and colorability. In particular, due to the excellent non-whitening property, whitening during bending can be prevented.

[0121] The molded product is preferably an injection molded product, a calendered product or a T-die extrusion molded product. In this case, it can have excellent mechanical properties such as impact strength, tensile strength and flexural strength, surface hardness, transparency, colorability and non-whitening property.

[0122] The molded article is preferably a film or a sheet. Specifically, the molded article may be a decorative sheet for decoration, a finishing material for outdoor building materials, or a finishing material for roofs.

[0123] The method for manufacturing a molded article preferably includes: kneading and extruding 35 wt % to 85 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 40 nm to 120 nm and 15 wt % to 65 wt % of a polymethacrylate resin (B) at 200° C. to 300° C. and 100 rpm to 500 rpm to obtain an extrudate; and performing injection molding, calendaring molding or T-die extrusion molding of the extrudate at a molding temperature of 180° C. to 300° C. to manufacture a molded article. In this case, excellent mechanical properties such as impact strength, tensile strength and flexural strength, surface hardness, transparency and colorability can be obtained. In particular, due to the excellent non-whitening property, whitening during bending can be prevented.

[0124] For example, the extrudate may be in the form of pellets or in the form of plates.

[0125] In this specification, when a plate-like shape is generally defined as a plate-like shape in the technical field to which the present invention pertains, the plate-like shape is not particularly limited, and the plate-like shape may include, for example, a flat shape, a sheet shape, a film shape, and the like.

[0126] Preferably, the step of manufacturing a molded article may include the step of calendering the prepared extrudate at a calendering temperature of 140° C. to 220° C. to obtain a sheet. In this case, excellent processability can be achieved, and a sheet having a uniform surface can be easily manufactured.

[0127] In this specification, calendaring is a method of rolling an extrudate using a calendaring device including a calendaring roll. Without specific restrictions, calendaring can be performed according to a method commonly used in the field to which the present invention belongs. Preferably, calendaring is performed according to a method comprising the following steps: a step of mixing thermoplastic resin particles as a sheet raw material at 130°C to 200°C using a mixer, a step of manufacturing a base sheet at 170°C to 200°C using the mixed raw materials, and a step of manufacturing a sheet at 140°C to 220°C using a base sheet and a calendaring roll. For example, the step of manufacturing a base sheet can be performed using a mixing roll.

[0128] The method for manufacturing a molded article may include the step of injection molding the prepared extrudate at an injection temperature of 200° C. to 260° C., an injection pressure of 60 bar to 100 bar, and a holding pressure of 25 bar to 55 bar. In this case, an injection molded article having excellent mechanical properties (e.g., impact strength) can be easily manufactured.

[0129] The injection temperature is preferably 200° C. to 230° C., more preferably 210° C. to 220° C. Within this range, an injection-molded article having excellent mechanical properties (eg, impact strength) can be easily produced.

[0130] The injection pressure is preferably 70 bar to 90 bar, more preferably 75 bar to 85 bar. Within this range, an injection molded product having excellent mechanical properties (eg, impact strength) can be easily manufactured.

[0131] The holding pressure is preferably 30 bar to 50 bar, more preferably 35 bar to 50 bar. Within this range, an injection molded product having excellent mechanical properties (eg, impact strength) can be easily manufactured.

[0132] The step of manufacturing a molded article may include a step of performing T-die extrusion molding of the prepared extrudate at an extrusion temperature of 200° C. to 300° C., an extrusion screw speed of 50 rpm to 200 rpm, a 3-axis roller temperature of 60° C. to 100° C., and a roller rotation speed of 1 m / min to 5 m / min. In this case, excellent processability can be achieved, and a sheet having a uniform surface can be easily manufactured.

[0133] When describing the thermoplastic resin composition of the present invention, the method for preparing the thermoplastic resin composition, and the molded article including the thermoplastic resin composition, it should be noted that other conditions or equipment not explicitly described herein may be appropriately selected within the range generally practiced in the art without particular limitation.

[0134] Hereinafter, the present invention will be described in more detail with reference to the following preferred embodiments. However, these embodiments are provided for illustrative purposes only, and should not be construed as limiting the scope and spirit of the present invention. In addition, it will be apparent to those skilled in the art that, without departing from the spirit and scope of the present invention, various changes and modifications may be made, and such changes and modifications are also within the scope of the appended claims.

[0135] Example

[0136] The materials used in Examples and Comparative Examples are as follows.

[0137] *ASA graft copolymer (A-1): An ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 100 nm prepared by emulsion polymerization (core: 38 wt% butyl acrylate and 7 wt% styrene, shell: 4 wt% butyl acrylate, 40 wt% styrene and 11 wt% acrylonitrile, degree of grafting: 70%).

[0138] *ASA graft copolymer (A-2): An ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 100 nm prepared by emulsion polymerization (core: 32 wt% butyl acrylate and 13 wt% styrene, shell: 4 wt% butyl acrylate, 40 wt% styrene and 11 wt% acrylonitrile, degree of grafting: 70%).

[0139] *ASA graft copolymer (A-3): An ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 100 nm prepared by emulsion polymerization (core: 37 wt% butyl acrylate and 3 wt% styrene, shell: 12 wt% butyl acrylate, 37 wt% styrene and 11 wt% acrylonitrile, degree of grafting: 120%).

[0140] *ASA graft copolymer (A-4): An ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 150 nm prepared by emulsion polymerization (core: 30 wt% butyl acrylate, shell: 12 wt% butyl acrylate, 47 wt% styrene and 11 wt% acrylonitrile, grafting degree: 70%).

[0141] *ASA graft copolymer (A-5): An ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 100 nm prepared by emulsion polymerization (core: 30 wt% butyl acrylate, shell: 12 wt% butyl acrylate, 47 wt% styrene and 11 wt% acrylonitrile, grafting degree: 70%).

[0142] *ASA graft copolymer (A-6): An ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 30 nm prepared by emulsion polymerization (core: 38 wt% butyl acrylate and 7 wt% styrene, shell: 4 wt% butyl acrylate, 40 wt% styrene and 11 wt% acrylonitrile, degree of grafting: 70%).

[0143] *ASA graft copolymer (A-7): An ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 150 nm prepared by emulsion polymerization (core: 38 wt% butyl acrylate and 7 wt% styrene, shell: 4 wt% butyl acrylate, 40 wt% styrene and 11 wt% acrylonitrile, degree of grafting: 70%).

[0144] *ASA graft copolymer (A-8): ASA graft copolymer containing alkyl acrylate rubber having an average particle size of 100 nm prepared by emulsion polymerization (core: 45 wt% butyl acrylate, shell: 44 wt% styrene and 11 wt% acrylonitrile, grafting degree: 50%).

[0145] * Polymethacrylate resin (B-1): polymethyl methacrylate resin with a weight average molecular weight of 80,000 g / mol (IF850, LG MMA)

[0146] *Styrene-acrylonitrile resin (B-2): 90HR (weight average molecular weight: 100,000 g / mol, LG Chemical Co., Ltd.).

[0147] Examples 1 to 7 and Comparative Examples 1 to 8

[0148] According to the contents shown in Tables 1 and 2, the components shown in Tables 1 and 2 were fed into a twin-screw extruder. At this time, 1 part by weight of a pentaerythritol derivative (Pasflow7501, Patechfine Chemical) as a lubricant, 0.5 parts by weight of Irgonox 1076 (BASF) and Irgafos 168 (BASF) as antioxidants, and 1 part by weight of Tinuvin 770 (BASF) and Sunsorb 329 (Sunfine Global) as UV stabilizers were fed into the twin-screw extruder. Then, melt kneading and extrusion were performed at 230° C. and 150 rpm to prepare pellets. Using the prepared pellets, the coverage value of alkyl acrylate was measured. Then, the prepared pellets were injected using an injection molding machine (Victory 330 / 80, Engel) at a molding temperature of 220°C, an injection pressure of 50 bar, and a holding pressure of 35 bar to obtain a sample for measuring appearance and physical properties. The sample was used to measure impact strength, tensile strength, flexural strength, surface hardness, gloss, light transmittance, and haze. In addition, a T-die extruder (Techline 20T, screw: 20 mm, L / D = 25, Collins) was used to extruder the pellets at a molding temperature of 230°C, an injection pressure of 200 kgf / cm 2 The film was extruded at a molding pressure of 100° C., a roll temperature of 85° C., and a roll rotation speed of 3.5 m / min to obtain a film having a thickness of 0.15T, and the non-whitening property was evaluated.

[0149] Test Case

[0150] The properties of the injection specimens and extrusion specimens prepared in Examples 1 to 7 and Comparative Examples 1 to 8 were measured according to the following methods, and the results are shown in Tables 1 and 2 and Figure 1 middle.

[0151] Measurement method

[0152] *Alkyl acrylate coverage value (%): The alkyl acrylate coverage value is calculated by the following Equation 1.

[0153] [Equation 1]

[0154] X = {(GY) / Y} × 100,

[0155] In Formula 1, G represents the gel content (wt%) based on the total weight of the thermoplastic resin composition, and Y represents the content (wt%) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition. 1 HNMR analysis or FT-IR analysis quantitatively measures the content of alkyl acrylate in the gel.

[0156] 1 H NMR

[0157] - Equipment name: Bruker 600MHz NMR (AVANCE III HD) CPP BB (1H 19F tunable, broadband, with z gradient) Prodigy probe

[0158] -Measurement conditions: 1 HNMR (zg30): ns=32, d1=5s, TCE-d2, at room temperature

[0159] FT-IR

[0160] -Device Name: Agilent Cary 660

[0161] -Measurement conditions: ATR mode

[0162] When measuring the gel content, 1 g of pellets obtained by extruding the thermoplastic resin composition was added to 30 g of acetone, and then stirred for 12 hours using an orbital shaker (equipment name: Lab companion SKC-6075) at 210 rpm and room temperature. Then, centrifuge (Supra R30, Hanil Scienece) was used at 0°C and 18,000 rpm for 3 hours to separate insoluble substances that were not dissolved in acetone, and then dried for 12 hours by forced circulation in a forced convection oven (equipment name: Lab companion OF-12GW) set at 85°C. Then, the gel content was measured and calculated by the following equation 2.

[0163] [Equation 2]

[0164] Gel content (%) = [weight of insoluble matter (gel) (g) / weight of sample (g)] × 100

[0165] *Grafting degree (%): 0.5 g of the powdered graft copolymer was added to 50 ml of acetone, stirred at room temperature for 12 hours, and centrifuged to separate the insoluble matter that was not dissolved in acetone, and then dried for 12 hours. The weight of the insoluble matter was measured, and the grafting degree was calculated by the following equation 3. The rubber weight is the weight (g) of the rubber component theoretically added to 0.5 g of the powdered graft copolymer.

[0166] [Equation 3]

[0167] Grafting degree (%) = [grafting monomer weight (g) / rubber weight (g)] × 100

[0168] In Equation 3, the weight (g) of the grafted monomer is obtained by subtracting the rubber weight (g) from the weight of the insoluble matter (gel) obtained by dissolving the grafted copolymer in acetone and centrifuging it, and the rubber weight (g) is the weight (g) of the rubber component theoretically added to the grafted copolymer powder.

[0169] Specifically, when measuring the weight (g) of insoluble matter (gel), 0.5 g of powdered graft copolymer was added to 50 ml of acetone, and then stirred for 12 hours using an orbital shaker (equipment name: Lab companion SKC-6075) at 210 rpm and room temperature. Then, centrifuge (Supra R30, Hanil Scienece) was used at 0 ° C and 18,000 rpm for 3 hours to separate the insoluble matter that was not dissolved in acetone, and then dried for 12 hours by forced circulation in a forced convection oven (equipment name: Lab companion OF-12GW) set at 85 ° C. Then, the weight of the insoluble matter (gel) was measured.

[0170] *Izod impact strength (kgf·cm / cm): Izod impact strength was measured at 23°C using a notched specimen (thickness: 1 / 4") in accordance with ASTM D256.

[0171] *Tensile strength (kgf / cm 2 ): The tensile strength was measured according to ASTM D638 using a specimen having a thickness of 3.2 mm at a crosshead speed of 10 mm / min.

[0172] *Flexural strength (kgf / cm 2): Flexural strength was measured according to ASTM D790 using a specimen with a thickness of 3.2 mm at a span of 64 mm and a test speed of 10 mm / min.

[0173] *Surface hardness: Rockwell hardness is measured on the R-scale according to ASTM D785.

[0174] *Gloss: Gloss is measured at 45° using a gloss meter according to ASTM D2457.

[0175] *Total light transmittance (Tt, %): The total light transmittance was measured according to ASTM D1003 using a test specimen having a thickness of 3T and a haze meter (HM-150, Murakami Lab Co., Ltd.).

[0176] *Haze (%): The haze was measured according to ASTM D1003 using a test specimen having a thickness of 3T and a haze meter (HM-150, MurakamiLab Co., Ltd.).

[0177] *Whether whitening occurs: An extruded sheet (thickness: 0.15T, width: 5 cm, length: 5 cm) was folded diagonally by hand. Then, whether whitening occurs on the bent surface was judged by visual observation, and non-whitening properties were evaluated as follows.

[0178] ○: No whitening occurs, indicating that the non-whitening property is excellent.

[0179] △: Whitening slightly occurs, indicating that the non-whitening property is moderate.

[0180] X: Whitening clearly occurs, indicating that the non-whitening property is inferior.

[0181] *Difference in haze by falling ball (Δ haze): A 1 kg weight was dropped vertically from a height of 25 cm onto an extruded film having a thickness, width, and length of 0.15 mm×5 cm×5 cm using a Gardner impact tester. Then, the haze values ​​of the portion of the film hit by the weight before and after the impact were measured according to ASTM D1003, and the haze difference was calculated by the following equation 4.

[0182] [Equation 4]

[0183] Haze difference (△ haze) = haze value after ball drop - haze value before ball drop

[0184] [Table 1]

[0185]

[0186] [Table 2]

[0187]

[0188] As shown in Tables 1 and 2, in the case of Examples 5 1 to 7 according to the present invention, mechanical properties such as impact strength, tensile strength and flexural strength, and surface hardness are excellent, compared to Comparative Examples 1 to 8 falling outside the present invention. In addition, due to the high gloss and total light transmittance, and high haze, transparency and colorability are excellent. In addition, due to the excellent non-whitening property, whitening during bending is prevented. Specifically, in the case of Comparative Example 1 containing an amount of ASA resin (A) less than the scope of the present invention, the impact strength is low, the haze increases, and whitening occurs. In the case of Comparative Example 2 containing an amount of ASA resin (A) exceeding the scope of the present invention, in addition to tensile strength, flexural strength and surface hardness, the gloss is reduced, resulting in reduced transparency.

[0189] Furthermore, in the case of Comparative Example 3 including ASA resin (A) having an alkyl acrylate coverage value less than the present invention range and the ASA resin containing an alkyl acrylate rubber having an average particle size greater than 120 nm, gloss, total light transmittance and haze were poor, and transparency decreased.

[0190] In addition, in the case of Comparative Example 4 including the styrene-acrylonitrile resin (B-2) instead of the polymethacrylate resin (B-1), the glossiness, total light transmittance, and haze were poor, and the transparency was reduced.

[0191] In addition, in the case of Comparative Example 5 including styrene-acrylonitrile resin (B-2) and ASA resin (A) having a grafting degree within the exemplary range of the present invention and having an alkyl acrylate coverage value less than the range of the present invention, total light transmittance and haze were poor, resulting in reduced transparency and occurrence of whitening.

[0192] In addition, in the case of Comparative Example 6 including an ASA resin containing an alkyl acrylate rubber having an average particle size of less than 50 nm, impact strength and total light transmittance were very poor. In the case of Comparative Example 7 including an ASA resin containing an alkyl acrylate rubber having an average particle size of more than 120 nm, whitening occurred, and the haze and haze difference increased.

[0193] Furthermore, in the case of Comparative Example 8 in which the coverage value of the alkyl acrylate was 50%, whitening occurred, and the haze difference increased.

[0194] In addition, if Figure 1 As shown, it can be seen that the occurrence of whitening is prevented in Examples 1, 2, 4 and 5 according to the present invention compared with Comparative Examples 3 to 5. In the case of Comparative Example 2, the occurrence of whitening is prevented, but the tensile strength, flexural strength and surface hardness are very low. Therefore, it is difficult to use the composition of Comparative Example 2 in the manufacture of products.

Claims

1. A thermoplastic resin composition, comprising: 35 to 85 wt% of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A), the graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50 to 120 nm; and 15 to 65 wt% of a polymethacrylate resin (B); The thermoplastic resin composition has an alkyl acrylate coverage value (X) of 70% or more as calculated by the following equation 1: [Equation 1] X = {(GY) / Y} × 100, wherein G represents the gel content in % by weight based on the total weight of the thermoplastic resin composition, and Y represents the content of the alkyl acrylate in the gel in % by weight based on the total weight of the thermoplastic resin composition, in, The polymethacrylate resin (B) has a weight average molecular weight of 50000 g / mol to 150000 g / mol, and Wherein, the polymethacrylate resin (B) is polymethyl methacrylate resin.

2. The thermoplastic resin composition according to claim 1, wherein The polymethacrylate resin (B) contains 55% by weight or more of a methacrylate monomer.

3. The thermoplastic resin composition according to claim 1, wherein The graft copolymer (A) comprises 20 to 60 wt % of an alkyl acrylate rubber (a-1) and 40 to 80 wt % of an aromatic vinyl compound-vinyl cyanide copolymer (a-2).

4. The thermoplastic resin composition according to claim 1, wherein The graft copolymer (A) has a grafting degree calculated by the following equation 3 of 60% or more: [Equation 3] Grafting degree (%) = [weight of grafted monomer in g / weight of rubber in g] × 100 wherein the weight of the graft monomer in g is obtained by subtracting the weight of the rubber in g from the weight of the insoluble matter in g as a gel obtained by dissolving the graft copolymer in acetone and subjecting it to centrifugation, and the rubber weight in g is the weight of the rubber component in g theoretically added to the graft copolymer powder.

5. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition comprises one or more selected from the group consisting of heat stabilizers, light stabilizers, colorants, anti-adhesive agents, antistatic agents, antibacterial agents, processing aids, metal deactivators, flame retardants, smoke suppressants, anti-drip agents, anti-friction agents and anti-wear agents.

6. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition comprises one or more selected from the group consisting of heat stabilizers, light stabilizers, dyes, pigments, anti-adhesive agents, antistatic agents, antibacterial agents, processing aids, metal deactivators, flame retardants, smoke suppressants, anti-drip agents, anti-friction agents and anti-wear agents.

7. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition comprises one or more selected from the group consisting of heat stabilizers, light stabilizers, colorants, lubricants, anti-adhesive agents, antistatic agents, antibacterial agents, metal deactivators, flame retardants, smoke suppressants, anti-drip agents, anti-friction agents and anti-wear agents.

8. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has a total light transmittance (Tt) of 75% or more as measured using a test specimen having a thickness of 3T according to ASTM D1003.

9. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has a haze of 11% or less as measured using a test specimen having a thickness of 3T according to ASTM D1003.

10. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has a gloss of 120 or more measured at an incident angle of 45° according to ASTM D2457.

11. The thermoplastic resin composition according to claim 1, wherein When a 1 kg weight is dropped vertically from a height of 25 cm onto an extruded film having dimensions of 0.15 mm×5 cm×5 cm in thickness, width and length using a Gardner impact tester, and the haze values ​​of a portion of the film hit by the weight before and after the impact are measured according to ASTM D1003 and the haze value difference is calculated, the thermoplastic resin composition has a haze difference of 10 or less.

12. A method for preparing a thermoplastic resin composition, the method comprising kneading and extruding 35 wt % to 85 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer (A) and 15 wt % to 65 wt % of a polymethacrylate resin (B) at 200° C. to 300° C. and 100 rpm to 500 rpm, wherein the graft copolymer (A) contains an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm, wherein the alkyl acrylate coverage value (X) of the thermoplastic resin composition calculated by the following equation 1 is 70% or more, [Equation 1] X = {(GY) / Y} × 100, wherein G represents the gel content in % by weight based on the total weight of the thermoplastic resin composition, and Y represents the content of the alkyl acrylate in the gel in % by weight based on the total weight of the thermoplastic resin composition, in, The polymethacrylate resin (B) has a weight average molecular weight of 50000 g / mol to 150000 g / mol, and Wherein, the polymethacrylate resin (B) is polymethyl methacrylate resin. 13 . A molded article comprising the thermoplastic resin composition according to claim 1 .